SCRUM: application experience in a software development PyME in the NEA - Barrios, Walter G. (2012)
In order to manage projects efficiently, agile methodologies for software development tools that improve production processes have emerged. This paper discusses the adaptation and implementation of the SCRUM methodology in a software development company of the NEA (Northeast Argentina) used under a strategic management approach, redesigned for its use in a microenterprise. The challenge was to achieve an effective technological linkage (between management and systems) oriented to the innovation in simplifying and streamlining roles in implementing the methodology. In the paper, we introduce the subject theoretically and then expose the practical aspects of the case and analyze the results.